High-compaction sodium vanadium phosphate positive electrode material and preparation method thereof
By mixing two sodium vanadium phosphate materials with different particle sizes and morphology and performing secondary sintering, a high-pressure sodium vanadium phosphate positive electrode material was prepared, which solved the problem of low compaction density of positive electrode material in the prior art and improved the Energy density, power density and rate performance.
Patent Information
- Application Number
- CN202411439102.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-18
AI Technical Summary
The existing sodium ion battery positive electrode materials have low compaction density, low energy density, low power density and poor rate performance, which limits its large-scale development.
High-pressure is prepared by mixing the first vanadium phosphate material with large particles, irregular morphology and loose and porous particles with the second vanadium phosphate material with smaller particles and undergoing secondary sintering. Sodium vanadium phosphate positive electrode material.
It improves the compaction density of sodium vanadium phosphate positive electrode material, enhances its energy density and power density, and improves the rate performance, and is suitable for sodium ion secondary batteries.
Smart Images

Figure CN119461297A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a high-density sodium vanadium phosphate positive electrode material and a preparation method thereof, belonging to the positive electrode direction of sodium ion batteries in the technical field of sodium electric new energy materials. Background Art
[0002] Sodium-ion batteries are expected to be widely used in electric bicycles, low-speed electric vehicles, energy storage, etc., due to their abundant sodium resources, low cost, good safety, excellent low-temperature performance, and fast charging performance. However, a series of problems such as low compaction density, low energy density, low power density, and poor rate performance have become important reasons for restricting their large-scale development.
[0003] The sodium vanadium phosphate cathode material with NASICON structure has the dual advantages of high rate performance and cycle performance. At present, the compaction density of sodium vanadium phosphate on the market is 1.6-1.8 g / cm 3 The 0.1C discharge specific capacity is generally around 105 mAh / g, and there is not much room for improvement.
[0004] In view of the requirements of the existing technology for the development of sodium ion batteries, there is an urgent need for electrode materials with high compaction density and good performance, and there are no articles or patents reporting the application of high compaction sodium vanadium phosphate in the preparation of sodium ion positive electrode materials. Therefore, increasing the compaction density of sodium vanadium phosphate can not only increase its energy density but also improve its processing performance, which has great value in sodium ion secondary batteries. Summary of the invention
[0005] The present invention aims to solve the problems existing in the prior art and provides a high-density sodium vanadium phosphate positive electrode material. The compaction density of the sodium vanadium phosphate positive electrode material is 2.00 g / cm 3 As mentioned above, the sodium vanadium phosphate positive electrode material is made into a button battery and the 0.1C discharge specific capacity is detected to be above 110 mAh / g.
[0006] The present invention also provides a new method for preparing the above-mentioned sodium vanadium phosphate positive electrode material, wherein the first sodium vanadium phosphate positive electrode material with larger particles, irregular morphology, loose and porous prepared and the second sodium vanadium phosphate material with smaller particles and dense prepared are uniformly mixed and then subjected to secondary sintering to prepare a high-density sodium vanadium phosphate positive electrode material, and the specific process comprises the following steps: (1) Preparation of the first sodium vanadium phosphate material: Weigh a certain amount of ammonium metavanadate, anhydrous sodium carbonate, ammonium dihydrogen phosphate, ethylene glycol and an organic complexing agent, and disperse them completely in deionized water by heating and stirring to obtain a uniform sodium vanadium phosphate composite precursor dispersion, and vaporize the solvent by spray drying to obtain a sodium vanadium phosphate composite solid precursor. Weigh a certain mass of the sodium vanadium phosphate composite solid precursor and place it in corundum, calcine it in a tube furnace, heat it under a protective atmosphere, wait for it to naturally cool to room temperature, then take it out, air flow crush it and mix it evenly, then pour the crushed powdered solid into a sieve to sieve it, and obtain the first sodium vanadium phosphate material with large particles, irregular morphology and loose and porous.
[0007] (2) Preparation of the second sodium vanadium phosphate material: Add vanadium pentoxide, sodium dihydrogen phosphate, glucose and zirconium-containing compounds to the solvent, stir thoroughly to obtain a reddish brown turbid liquid, pour the reddish brown turbid liquid into a zirconium oxide ball mill, grind until the slurry D50 is 1-2 μm, filter to obtain a yellow-green solid, and after complete drying, crush it with a powder grinder and mix it evenly to obtain a sodium vanadium phosphate composite solid precursor. Weigh a certain mass of the sodium vanadium phosphate composite solid precursor and place it in corundum, place it in a tube furnace for calcination, heat it under a protective atmosphere, wait for it to naturally drop to room temperature, then take it out, air flow crush it and mix it evenly, then pour the crushed powdered solid into a sieve to obtain a second sodium vanadium phosphate material with smaller particles and more density.
[0008] (3) Preparation of sodium vanadium phosphate mixed material: The sodium vanadium phosphate materials described in steps (1) and (2) are mixed in a certain mass ratio to obtain a sodium vanadium phosphate mixed material.
[0009] (4) Preparation of sodium vanadium phosphate positive electrode material: The sodium vanadium phosphate mixed material in step (3) is subjected to secondary sintering to obtain a sodium vanadium phosphate positive electrode material.
[0010] In the above scheme, an organic complexing agent and ethylene glycol are added during the preparation of the first sodium vanadium phosphate material, and a stable complex is formed between the organic complexing agent and the metal ions through the strong ionization complexation, so that the particles are agglomerated with each other. At the same time, ethylene glycol not only serves as a carbon source, but also helps the organic complex to be evenly dispersed in deionized water, and sintered at high temperature to obtain the first sodium vanadium phosphate material with large particles, irregular morphology, and loose and porous particles; zirconium-containing compounds are added during the preparation of the second sodium vanadium phosphate material, and are evenly integrated into the material particles of the slurry through grinding, which can inhibit the growth of particles during the sintering process and make the particles aggregate densely, thereby improving the compaction density of the material, and obtaining the second sodium vanadium phosphate material with smaller and dense particles coated with metal zirconium ions; the compaction density and overall performance of the material are improved by mixing the two sodium vanadium phosphate materials and filling and penetrating each other in the secondary sintering.
[0011] In the above technical scheme, preferably, in the step (1), the molar ratio of ammonium metavanadate to anhydrous sodium carbonate is 1:1-1:3, the molar ratio of ammonium dihydrogen phosphate to anhydrous sodium carbonate is 1:1-3:1, the added ethylene glycol accounts for 2%-5% of the mass of ammonium metavanadate, and the organic complexing agent accounts for 0.1%-0.3% of the total mass of ammonium metavanadate, anhydrous sodium carbonate, ammonium dihydrogen phosphate and ethylene glycol.
[0012] In the above technical solution, preferably, in the step (1), the deionized water is added in an amount of 20%-30% of the solid content of the mixed slurry.
[0013] In the above technical scheme, preferably, in the step (1), the organic complex is one or more of ethylenediaminetetramethylenephosphonic acid sodium, diethylenetriaminepenta(methylenephosphonic acid) salt, aminotri(methylenephosphonic acid) salt, hydroxyethylidene diphosphonic acid sodium, sodium nitrilotriacetate, ethylenediaminetetraacetate, diethylenetriaminepentacarboxylate, polymaleic anhydride, polyacrylic acid, polyhydroxyacrylic acid, maleic acid acrylic acid copolymer, polyacrylamide, ethanolamine, diethanolamine, and triethanolamine.
[0014] In the above technical solution, preferably, in step (1), the heating solvent temperature is 45°C-100°C, the stirring speed is 300-2000 rmp, the heating and stirring time is 0.5-5 h, and the heating and stirring are required to be carried out until the solution is completely clear and there is no solid precipitation.
[0015] In the above technical solution, preferably, in step (1), the precursor material is spray dried by a spray dryer, a centrifugal spray dryer or a pressure spray dryer, the inlet temperature of the spray dryer is 200-350 °C, and the outlet temperature of the spray dryer is 60-120 °C. The spray drying fan is set to 75-95, the temperature is set to 160-250 °C, the peristaltic pump is set to 10-50 mL / min, and the needle is set to 5-15 s. The particle size of the outlet particles can be precisely controlled by adjusting the solution solid content and the spray drying parameters, and the particle size range is 2-10 μm.
[0016] In the above technical solution, preferably, in the steps (1) and (2), the heating rate is 2-10 °C / min. In particular, a staged calcination method can be used to fully increase the carbonization time. The heating rate of the first calcination is 2-10 °C / min, the first calcination temperature is 300-500 °C, the first calcination time is 2-5 h, and the heating rate of the second calcination is 2-10 °C / min, the second calcination temperature is 600-1000 °C, and the calcination time is 5-20 h.
[0017] In the above technical solution, preferably, in steps (1) and (2), the protective gas is argon, nitrogen, helium, neon or other inert gases, and the gas flow rate is 2-50 mL / min.
[0018] In the above technical solution, preferably, in step (2), the molar ratio of vanadium pentoxide, sodium dihydrogen phosphate and glucose is 4-8:12-24:1-2, the percentage of the added zirconium-containing compound to the mass of vanadium pentoxide is 0.3%-0.7%, and the stirring temperature is 20-40°C.
[0019] In the above technical solution, preferably, in step (2), the solvent is one or more of methanol, ethanol, ether, deionized water, n-propanol, N,N-dimethylformamide, acetone, ethyl acetate, and petroleum ether.
[0020] In the above technical solution, preferably, in the step (2), the amount of solvent added is 30%-40% of the solid content of the slurry after mixing.
[0021] In the above technical solution, preferably, in the step (2), the zirconium-containing compound is one or more of zirconium trichloride, zirconium tetrachloride, zirconium oxychloride, butyl zirconate, and zirconium aminophthalate.
[0022] In the above technical solution, preferably, in the step (2), the mass ratio of the reddish brown turbid liquid to the zirconia balls is 1.10-1.50, and the diameter of the zirconia balls is 2-3 mm. In particular, low-speed pre-grinding can be adopted to make the materials mixed more evenly, with a pre-grinding speed of 100 r / min and a time of 1 h. After the pre-grinding is completed, the speed is adjusted to 400-1000 r / min and the ball milling is performed for 2-6 h.
[0023] In the above technical solution, preferably, in step (2), the drying method is vacuum drying or forced air drying, the drying temperature is 60-120°C, and the drying time is 6-10 h.
[0024] In the above technical solution, preferably, the sieving mesh number in step (2) is 200-350 meshes.
[0025] In the above technical solution, preferably, in step (3), the mass ratio of the first and second sodium vanadium phosphate materials is 1:1-1:10.
[0026] In the above technical solution, preferably, in step (4), the sintering temperature is 300-600°C and the holding time is 4-6 h.
[0027] The present invention discloses a high-density sodium vanadium phosphate positive electrode material and a preparation method thereof. The positive electrode material is prepared by mixing and sintering two sodium vanadium phosphate materials with different particle sizes and morphologies in proportion. The sodium vanadium phosphate positive electrode material has a compaction density of 2.00 g / cm 3 As mentioned above, the button battery made of it has a 0.1C discharge capacity of more than 110 mAh / g, and has high compaction performance and electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XRD diagram of the first sodium vanadium phosphate material synthesized by the preparation method described in Example 1.
[0029] Figure 2 This is the XRD pattern of the second sodium vanadium phosphate material synthesized by the preparation method described in Example 1.
[0030] Figure 3 This is the XRD diagram of the sodium vanadium phosphate positive electrode material synthesized by the preparation method described in Example 1.
[0031] Figure 4 This is a particle size diagram of the first sodium vanadium phosphate material synthesized by the preparation method described in Example 1.
[0032] Figure 5 This is a particle size diagram of the second sodium vanadium phosphate material synthesized by the preparation method described in Example 1.
[0033] Figure 6 This is a particle size diagram of the sodium vanadium phosphate positive electrode material synthesized by the preparation method described in Example 1.
[0034] Figure 7 This is a SEM image of the first sodium vanadium phosphate material synthesized by the preparation method described in Example 1.
[0035] Figure 8 This is a SEM image of the second sodium vanadium phosphate material synthesized by the preparation method described in Example 1.
[0036] Fig. 9 This is a SEM image of the sodium vanadium phosphate positive electrode material synthesized by the preparation method described in Example 1.
[0037] Fig.10 This is a charge and discharge curve of the sodium vanadium phosphate positive electrode material synthesized by the preparation method described in Example 1 at a current density of 0.1C in the first week.
[0038] Fig.11 This is a cycle curve diagram of the sodium vanadium phosphate positive electrode material synthesized by the preparation method described in Example 1 at a current density of 1 C. DETAILED DESCRIPTION
[0039] In order to better understand the present invention, the content of the present invention is further described below in conjunction with embodiments and related drawings, but the content of the present invention is not limited to the following embodiments.
[0040] This embodiment provides a method for preparing a high-density sodium vanadium phosphate positive electrode material by mixing and sintering two sodium vanadium phosphate materials with different particle sizes and morphologies in proportion, and the specific steps are as follows: (1) Preparation of the first sodium vanadium phosphate material: 8 mmol of ammonium metavanadate and 6 mmol of anhydrous sodium carbonate were added to deionized water, the solid content was adjusted to 20%-30%, and the mixture was stirred at 60-90 °C until the ammonium metavanadate and sodium carbonate were completely dissolved to obtain a beige solution. 12 mmol of diammonium phosphate was slowly added, and the mixture was stirred until no obvious bubbles were generated in the solution. Then, 2%-5% of ethylene glycol was added to the mass percentage of ammonium metavanadate and 0.1%-0.3% of the total mass percentage of ammonium metavanadate, anhydrous sodium carbonate, diammonium phosphate, and ethylene glycol were added. The mixture was stirred continuously until the solution was dark green and clear. The inlet temperature of the spray dryer was 200-350 °C, and the outlet temperature of the spray dryer was 60-120 °C. The spray drying fan is set to 75-95, the temperature is set to 160-250 °C, the peristaltic pump is set to 10-50 mL / min, the needle is set to 5-15 s, and the precursor of the first sodium vanadium phosphate material is obtained by spray drying. The above sodium vanadium phosphate precursor is weighed and placed in corundum, and then placed in a tubular furnace for calcination. Under a protective atmosphere, the heating rate of the first calcination is 2-10 °C / min, the temperature is 300-500 °C, and the time is 2-5 h. The heating rate of the second calcination is 2-10 °C / min, the temperature is 600-1000 °C, and the time is 5-20 h. Wait for it to naturally drop to room temperature and then take it out, crush it with a jet mill and mix it thoroughly. Then pour the crushed powdered solid into the sieve and sieve it with a mesh size of 200-350 meshes to obtain the first sodium vanadium phosphate material with large particles, irregular morphology, and loose and porous.
[0041] (2) Preparation of the second sodium vanadium phosphate material: 4 mmol vanadium pentoxide, 12 mmol sodium dihydrogen phosphate, 1 mmol glucose and a zirconium-containing compound accounting for 0.3%-0.7% of the mass percentage of vanadium pentoxide are added to the solvent, and the solid content is adjusted to 30%-40%. After sufficient stirring, a reddish-brown turbid liquid is obtained, and the reddish-brown turbid liquid is poured into a zirconia ball mill, the mass ratio of the reddish-brown turbid liquid to the zirconia ball is 1.10-1.50, and the diameter of the zirconia ball is 2-3 mm. Pre-grind at a speed of 100 r / min for 1 hour, adjust the speed to 400-1000 r / min, ball mill for 2-6 hours, grind until the slurry D50 is 1-2 μm, filter, and obtain a yellow-green solid. After complete drying, crush it with a powder grinder and mix it evenly to obtain the second sodium vanadium phosphate material precursor. The sodium vanadium phosphate precursor is weighed and placed in corundum, and then calcined in a tubular furnace. Under a protective atmosphere, the heating rate of the first calcination is 2-10 °C / min, the temperature is 300-500 °C, and the time is 2-5 h. The heating rate of the second calcination is 2-10 °C / min, the temperature is 600-1000 °C, and the time is 5-20 h. After waiting for it to naturally drop to room temperature, it is taken out, crushed with a jet mill and fully mixed. Then the crushed powdered solid is poured into a sieve and sieved with a mesh size of 200-350 to obtain a second sodium vanadium phosphate material with smaller particles and denseness.
[0042] (3) Preparation of sodium vanadium phosphate mixed material: The sodium vanadium phosphate materials described in steps (1) and (2) are mixed at a mass ratio of 1:1-1:10 to obtain a sodium vanadium phosphate mixed material.
[0043] (4) Preparation of sodium vanadium phosphate positive electrode material: Weigh the sodium vanadium phosphate mixed material in step (3) and place it in corundum, and then calcine it in a tube furnace. Under a protective atmosphere, the calcination heating rate is 3-5 °C / min, the temperature is 300-500 °C, and the time is 2-5 h to obtain a high-density sodium vanadium phosphate positive electrode material.
[0044] Example 1 Based on the above implementation, this embodiment provides a specific method for preparing a high-density sodium vanadium phosphate positive electrode material by mixing and sintering two sodium vanadium phosphate materials with different particle sizes and morphologies in proportion. (1) Preparation of the first sodium vanadium phosphate material: solid content is 20%, stirring temperature is 80 °C, the added ethylene glycol accounts for 4% of the mass of ammonium metavanadate, and the added organic complexing agent is aminotrimethylphosphonate, accounting for 0.3% of the total mass of the slurry. The spray dryer inlet temperature is 220 °C, the spray dryer outlet is 90 °C, the spray dryer fan is set to 75, the temperature is set to 180 °C, the peristaltic pump is set to 32mL / min, and the needle is set to 10 s. The protective atmosphere is nitrogen, the primary calcination heating rate is 5 °C / min, the temperature is 450 °C, the time is 3 h, and the secondary calcination heating rate is 2 °C / min, the temperature is 870 °C, and the time is 10 h.
[0045] By the attached Figure 1 The data show that the first sodium vanadium phosphate material obtained by the present invention has no obvious impurity peaks compared with the standard card, and the obtained product is sodium vanadium phosphate. Figure 4 The data show that the D50 of the first sodium vanadium phosphate material obtained by the present invention is 17.116 μm. Figure 7 The data show that the first sodium vanadium phosphate positive electrode material obtained by the present invention has irregular clusters inside and naturally formed holes on the surface. In the process of preparing the first sodium vanadium phosphate positive electrode material, the added organic complexing agent aminotrimethylphosphonate is evenly dispersed in deionized water, so that the intermolecular hydrogen bonds bind to the vanadium metal ions to form a stable complex, thereby agglomerating the particles with each other, thereby increasing the particle size of the material and forming large particles, irregular morphology, loose and porous cluster particles.
[0046] (2) Preparation of the second sodium vanadium phosphate material: solid content is 40%, stirring temperature is 20 °C, the zirconium-containing compound added is zirconium aminophthalate, accounting for 0.5% of the mass percentage of vanadium pentoxide. The mass ratio of reddish brown turbid liquid to zirconium oxide balls is 1.10, the diameter of zirconium oxide balls is 3 mm, the rotation speed is 800 r / min, the ball milling time is 4 h, the protective atmosphere is nitrogen, the first calcination heating rate is 3 °C / min, the temperature is 500 °C, the time is 4 h, the second calcination heating rate is 2 °C / min, the temperature is 730 °C, and the time is 12 h.
[0047] By the attached Figure 2 The data show that the second sodium vanadium phosphate positive electrode material obtained in the present invention has no obvious impurity peaks compared with the standard card, and the obtained product is sodium vanadium phosphate. Figure 5 The data show that the D50 of the second sodium vanadium phosphate positive electrode material obtained in the present invention is 1.887 μm. Figure 8The data show that the second sodium vanadium phosphate positive electrode material obtained by the present invention has compact and dispersed coral-like particles inside. During the preparation of the second sodium vanadium phosphate material, zirconium aminophthalate is added and evenly integrated into the material particles of the slurry through grinding. During the sintering process, the growth of particles can be inhibited and the particles can be aggregated and compacted, thereby obtaining the second sodium vanadium phosphate material with smaller and dense particles coated with metal zirconium ions.
[0048] (3) Preparation of sodium vanadium phosphate mixed material: The mass ratio of the first sodium vanadium phosphate material to the second sodium vanadium phosphate material is 1:4.
[0049] (4) Preparation of sodium vanadium phosphate positive electrode material: The protective atmosphere was nitrogen, the calcination heating rate was 4 °C / min, the temperature was 400 °C, and the time was 5 h, resulting in a high-density, high-performance sodium vanadium phosphate positive electrode material.
[0050] By the attached Figure 3 The data show that the secondary sintered sodium vanadium phosphate mixed material obtained by the present invention has no obvious impurity peaks compared with the standard card, and the obtained product is sodium vanadium phosphate. Figure 6 It can be seen that the D50 of the secondary sintered sodium vanadium phosphate mixed material obtained by the present invention is 7.008 μm. Fig. 9 It can be seen that the secondary sintered sodium vanadium phosphate mixed material obtained by the present invention has compact, irregular block particles inside.
[0051] From the above analysis, it can be seen that when the mixed calcination temperature is 400 ℃ and the calcination time is 5 h, the obtained sodium vanadium phosphate cathode material has the highest compaction density and the best electrochemical performance. The difference in particle size and morphology characteristics of the two sodium vanadium phosphate cathode materials provides conditions for the grading of the materials. After secondary sintering, the small particles and large particles can be more closely combined. In addition, there is a certain space inside the material, which is not only conducive to the infiltration of the electrolyte, but also conducive to the deintercalation of sodium ions, thereby increasing the compaction density of the material and improving the electrochemical performance of the material.
[0052] Example 2 The difference between Example 2 and Example 1 is that the mass ratio of the first sodium vanadium phosphate material to the second sodium vanadium phosphate material is 1:1.
[0053] Example 3 The difference between Example 3 and Example 1 is that the mass ratio of the first sodium vanadium phosphate material to the second sodium vanadium phosphate material is 1:10.
[0054] Example 4 The difference between Example 4 and Example 1 is that the mass ratio of the first sodium vanadium phosphate material to the second sodium vanadium phosphate material is 1:12.
[0055] Example 5 The difference between Example 5 and Example 1 is that in the preparation of the first sodium vanadium phosphate material, the complexing agent is diethylenetriamine pentacarboxylate.
[0056] Example 6 The difference between Example 6 and Example 1 is that in the preparation of the second sodium vanadium phosphate material, the zirconium-containing compound is butyl zirconate.
[0057] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the second sodium vanadium phosphate material is not used as the mixed raw material, and only step (1) is implemented.
[0058] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the first sodium vanadium phosphate material is not used as the mixed raw material, and only step (2) is implemented.
[0059] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that no organic complexing agent is added in the preparation of the first sodium vanadium phosphate material, and the particle size of the obtained first sodium vanadium phosphate material is 13.445 μm.
[0060] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that no zirconium-containing compound is added in the preparation of the second sodium vanadium phosphate material, and the particle size of the obtained second sodium vanadium phosphate material is 5.778 μm.
[0061] Table 1 shows the battery performance of sodium vanadium phosphate positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-4
[0062] From Table 1 and Appendix Fig.10 The data show that when the mass ratio of the first sodium vanadium phosphate material to the second sodium vanadium phosphate material in Example 1 is 1:4, the compaction density of the sodium vanadium phosphate positive electrode material is the largest, which is 2.28 g / cm 3 ; The discharge specific capacity at 0.1C current density is the highest, which is 115.8 mAh / g, and the 1 C / 0.2 C rate performance is 99.6%, showing excellent electrochemical performance. When the sodium vanadium phosphate positive electrode material is not graded, the compaction density of the first sodium vanadium phosphate positive electrode material is 1.73 g / cm 3 ; The discharge capacity at 0.1C current density is 107.5 mAh / g; The compaction density of the second sodium vanadium phosphate positive electrode material is 1.84 g / cm 3; The discharge capacity at 0.1C current density is 108.1 mAh / g; which is lower than the battery performance after the first sodium vanadium phosphate material and the second sodium vanadium phosphate material are graded. It can be seen that the method of preparing a high-density high-performance sodium vanadium phosphate positive electrode material by mixing and sintering two sodium vanadium phosphate materials with different particle sizes and morphologies in proportion can significantly improve the compaction density and discharge capacity of the battery.
[0063] By the attached Fig.11 The data show that the capacity retention rate of the mixed secondary sintered sodium vanadium phosphate positive electrode material prepared by the present invention is still 99% after 200 cycles at a current density of 1 C, and the material exhibits excellent cycle performance.
[0064] From the above data, it can be seen that the preparation method of the positive electrode material for high-pressure compaction sodium ion battery provided by the present invention has a simple preparation process and is easy to operate. The obtained sodium vanadium phosphate positive electrode material has good crystallinity, high electrochemical capacity, good cycle stability, high compaction density, and good processability, and has good application value in sodium ion secondary batteries.
[0065] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-density sodium vanadium phosphate positive electrode material, characterized in that: The steps include: (1) Preparation of the first sodium vanadium phosphate material: ammonium metavanadate, anhydrous sodium carbonate, ammonium dihydrogen phosphate, ethylene glycol and an organic complexing agent are completely dispersed in deionized water by heating and stirring to obtain a uniform sodium vanadium phosphate composite precursor dispersion, which is spray-dried to obtain a sodium vanadium phosphate composite solid precursor, and a certain mass of the sodium vanadium phosphate composite solid precursor is weighed and calcined to obtain the first sodium vanadium phosphate material; (2) Preparation of the second sodium vanadium phosphate material: adding vanadium pentoxide, sodium dihydrogen phosphate, glucose and a zirconium-containing compound to a solvent, stirring and grinding until the slurry D50 is 1-2 μm, filtering and drying to obtain a sodium vanadium phosphate composite solid precursor, and weighing a certain mass of the sodium vanadium phosphate composite solid precursor to obtain the second sodium vanadium phosphate material; (3) Preparation of sodium vanadium phosphate mixed material: mixing the sodium vanadium phosphate materials described in steps (1) and (2) in a certain mass ratio to obtain a sodium vanadium phosphate mixed material; (4) Preparation of sodium vanadium phosphate positive electrode material: The sodium vanadium phosphate mixed material in step (3) is subjected to secondary sintering to obtain a sodium vanadium phosphate positive electrode material.
2. The method for preparing the high-density sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the molar ratio of ammonium metavanadate to anhydrous sodium carbonate is 1:1-1:3, the molar ratio of ammonium dihydrogen phosphate to anhydrous sodium carbonate is 1:1-3:1, the added ethylene glycol accounts for 2%-5% of the mass of ammonium metavanadate, and the organic complexing agent accounts for 0.1%-0.3% of the total mass of ammonium metavanadate, anhydrous sodium carbonate, ammonium dihydrogen phosphate and ethylene glycol. In the step (1), the heating solvent temperature is 45°C-100°C, the stirring speed is 300-2000 rmp, and the heating and stirring time is 0.5-5 h.
3. The method for preparing the high-density sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the organic complexing agent is one or more of ethylenediaminetetramethylenephosphonic acid sodium, diethylenetriaminepenta(methylenephosphonic acid) salt, aminotri(methylenephosphonic acid) salt, hydroxyethylidene diphosphonic acid sodium, sodium nitrilotriacetate, ethylenediaminetetraacetate, diethylenetriaminepentacarboxylate, polymaleic anhydride, polyacrylic acid, polyhydroxyacrylic acid, maleic acid acrylic acid copolymer, polyacrylamide, ethanolamine, diethanolamine, and triethanolamine.
4. The method for preparing the high-density sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the precursor material is spray dried by a spray dryer, a centrifugal spray dryer or a pressure spray dryer, the inlet temperature of the spray dryer is 200-350°C, the outlet temperature of the spray dryer is 60-120°C, the spray drying fan is set to 75-95, the temperature is set to 160-250°C, the peristaltic pump is set to 10-50 mL / min, and the needle is set to 5-15 s. The particle size of the outlet particles can be precisely controlled by adjusting the solution solid content and the spray drying parameters, and the particle size range D50 is 2-10 μm.
5. The method for preparing the high-density sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: During the calcination process of steps (1) and (2), calcination is carried out under a protective gas atmosphere, wherein the protective gas is argon, nitrogen, helium, neon or other inert gases, and the gas flow rate is 2-50 mL / min. In steps (1) and (2), the heating rate is 2-10°C / min. In particular, a staged calcination method can be used to fully increase the carbonization time. The heating rate of the first calcination is 2-10°C / min, the first calcination temperature is 300-500°C, and the first calcination time is 2-5 h. The heating rate of the second calcination is 2-10°C / min, the second calcination temperature is 600-1000°C, and the calcination time is 5-20 h.
6. The method for preparing the high-density sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: In the step (2), the molar ratio of vanadium pentoxide, sodium dihydrogen phosphate and glucose is 4-8:12-24:1-2, the percentage of the added zirconium-containing compound to the mass of vanadium pentoxide is 0.3%-0.7%, the stirring temperature is 20-40°C, and the zirconium-containing compound is one or more of zirconium trichloride, zirconium tetrachloride, zirconium oxychloride, butyl zirconate and zirconium aminophthalate.
7. The method for preparing the high-density sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: In the step (2), the solvent is one or more of methanol, ethanol, ether, deionized water, n-propanol, N,N-dimethylformamide, acetone, ethyl acetate, and petroleum ether, and the amount of solvent added is 30%-40% of the solid content of the mixed slurry.
8. The method for preparing the high-density sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: In the step (2), the mass ratio of the reddish brown turbid liquid to the zirconium oxide balls is 1.10-1.50, and the diameter of the zirconium oxide balls is 2-3 mm. In particular, low-speed pre-grinding can be adopted to make the materials mixed more evenly. The pre-grinding speed is 100 r / min and the time is 1 h. After the pre-grinding is completed, the speed is adjusted to 400-1000 r / min and the ball milling is carried out for 2-6 h.
9. The method for preparing the high-density sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: In the step (3), the mass ratio of the first and second sodium vanadium phosphate materials is 1:1-1:
10. In the step (4), the sintering temperature is 300-600°C and the holding time is 4-6 h.
10. A high-density sodium vanadium phosphate positive electrode material, characterized in that The method according to any one of claims 1 to 9, wherein the compacted density is 2.00 g / cm 3 above.